2007
DOI: 10.1007/bf02922082
|View full text |Cite
|
Sign up to set email alerts
|

Univalence criteria for lifts of harmonic mappings to minimal surfaces

Abstract: A general criterion in terms of the Schwarzian derivative is given for global univalence of the Weierstrass-Enneper lift of a planar harmonic mapping. Results on distortion and boundary regularity are also deduced. Examples are given to show that the criterion is sharp. The analysis depends on a generalized Schwarzian defined for conformal metrics and on a Schwarzian introduced by Ahlfors for curves. Convexity plays a central role.2000 Mathematics Subject Classification. Primary 30C99; Secondary 31A05, 53A10. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…In [4] we generalized Nehari's univalence criterion to the (conformal) lift f of a harmonic mapping f to its associated minimal surface Σ. Under an inequality of the form…”
Section: Its Most Important Property Is Möbius Invariance: S(t • F ) mentioning
confidence: 99%
See 1 more Smart Citation
“…In [4] we generalized Nehari's univalence criterion to the (conformal) lift f of a harmonic mapping f to its associated minimal surface Σ. Under an inequality of the form…”
Section: Its Most Important Property Is Möbius Invariance: S(t • F ) mentioning
confidence: 99%
“…In earlier work [4] we obtained the following criterion for the lift of a harmonic mapping to be univalent. 8…”
Section: Its Most Important Property Is Möbius Invariance: S(t • F ) mentioning
confidence: 99%
“…In particular, the authors of [5] observed a deep connection of S f with lifts of harmonic functions onto minimal surfaces. In [15,16] some estimations of S f in some subclasses of univalent harmonic functions were obtained and many properties of the Schwarzian were established.…”
Section: S[h](z)| ≤ 2p(|z|) In Dmentioning
confidence: 99%
“…On the other hand, a generalization of the univalence criteria of Nehari (1) is proven in [4]. In that article is shown that, if f = h +ḡ is harmonic in D, its dilatation is the square of some meromorphic function, and…”
Section: Introductionmentioning
confidence: 96%